Prevalence of Burnout Syndrome among professors of the State School in Niterói, Brazil - Lima da Silva, Jorge Luiz (2017)
The objective of this study was to describe the prevalence of Burnout Syndrome among the professors of the State School in Niterói, Brazil. It is a quantitative, descriptive study, with information from a survey conducted with teachers. The questionnaire used consisted of closed questions that addressed the sociodemographic characteristics and work characteristics of the research subjects and the Maslach Burnout Inventory. Suspected prevalence of burnout syndrome according to Grunfeld's criteria was 33 cases (63.5%). The significant prevalence of this syndrome among teachers generates alert about working conditions and the mental health of these professionals. It is concluded that, from the data analyzed, it was observed that the profession lacks interventions to improve the quality of life of teachers in their work.